Worry and Depression in the Old and Young: Differences and Mediating Factors. Issue 4 (20th November 2014) - Armstrong, Lucy; Wuthrich, Viviana M.; Knight, Ashleigh; Joiner, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: This study examined whether differences in habitual negative self-thinking and coping strategies might contribute to the age differences in worry and depression. Method: 60 undergraduate students (age range: 18–24 years, M = 19.10, SD = 1.3) and 45 community-dwelling older adults (age range: 60–89 years, M = 73.5, SD = 7.5) participated. Participants completed self-report measures of worry, depression, negative self-thinking, and coping styles. Results: We replicated previous findings that older adults were less worried and less depressed than younger adults. Older adults also reported engaging in less habitual negative thinking and using more problem solving as a coping strategy than younger adults. Furthermore, negative self-thinking and problem-solving skills were found to partially mediate age differences in worry and fully mediate depression scores. Conclusions: These results suggest that habitual negative thinking and problem-solving skills play a role in explaining the lower rates of worry and depression in older populations.